Metabolomic and Growth Responses of Houttyunia cordata to Varying Light Intensities and Subsequent Effects on Fermented Products - Boonchaisri, Siriwat; Mokoed, Chutima; Phuangchaona, Phanumat; Treenate, Ekawit (Trends in Sciences, 2024)
Suitable light intensities were studied to enable sustainable and efficient cultivation of Houttuynia cordata with a high yield of bioactive compounds which later can be a good quality material for fermentation. To achieve this goal, the evaluation of physiological adaptation and elucidation of the metabolic alterations of Houttuynia cordata in response to different light intensities were conducted. Four-month-old H. cordata was exposed to 3 different light intensities: high light, control, and low light (100, 50 and 20 % natural irradiances, respectively). Physiological responses were measured using leaf gas exchange. The same leaf samples were either methanolic extracted for LC-QTOF-MS analysis to generate metabolite fingerprints or fermented for 3 months prior to quercetin quantification. High light treatment had the greatest effects on both the physiology and metabolisms of H. cordata compared to control and low light treatments. Compared to the control, the key results observed in high-light-grown H. cordata were a significant increase in photosynthesis, a decrease in relative chlorophyll contents, the enrichment of the top 3 metabolic pathways (phenylpropanoid biosynthesis, pyruvate metabolism and fatty acid degradation) and increasing quercetin concentrations in both fresh and fermented leaves. Metabolite fingerprints of high light-grown H. cordata were distinctively different from those of the other 2 treatments according to PCA and hierarchical clustering analysis. In conclusion, H. cordata responded to high light intensity by enriching the phenylpropanoid biosynthetic pathway to elevate sunscreen pigments. Additional acetyl-CoA generated from pyruvate metabolism and fatty acid degradation was a key supporting factor in the above response. As high quercetin concentration was observed in both fresh and fermented leaves, this will lead to quality improvement of the fermented products. HIGHLIGHTS The remarkable effects of light intensities on Houttuynia cordata growth and abundance of bioactive compounds are substantial, but the underlying mechanism has never been investigated. Metabolomics technology was applied to gain insight into light-induced metabolic reconfiguration. GRAPHICAL ABSTRACT